Strength at the Interface of CNT Films Made by Surface Decomposition of SiC - Yosuke Tsukiyama (Japanese Society of Tribologists, 2008)
Adherence of carbon nanotube film made by surface decomposition of SiC was studied. For this purpose we carried out scratch tests in nano- and microscale. By microscratch test, it was found that adherence at the interface was higher for CNT films with shorter CNTs and CNTs were not broken at the middle but removed from the interface. To clarify the dominant force (shear force or moment of force) which caused different adherence, we also carried out nanoscratch test by using AFM. In nanoscratch, AFM tip made of diamond coated silicon applied shear force to CNT films from lateral direction. And there was no significant change of adherence by lateral force (shear force at the interface). We conclude that bending-induced moment of force is dominant on the interface strength of CNT films.